Clinical applications of dual‐channel transmit MRI: A review. Issue 4 (9th April 2015) - Brink, Wyger M.; Gulani, Vikas; Webb, Andrew G.
<x xml:space="preserve">Abstract</x> This article reviews the principle of dual‐channel transmit MRI and highlights current clinical applications which are performed primarily at 3 Tesla. The main benefits of dual‐channel transmit compared with single‐transmit systems are the increased image contrast homogeneity and the decreased scanning time due to the more accurate local specific absorption ratio estimation, meaning that less conservative safety limits are needed. The dual‐transmit approach has been particularly beneficial in body imaging applications, and is also promising in terms of cardiac, spine, and fetal imaging. Future advances in transmit SENSE, the combination of dual‐channel transmit with high permittivity pads, as well as the potential increase in the number of transmit channels are also discussed. J. Magn. Reson. Imaging 2015;42:855–869.